Effects of Gender Roles on Food Security among Rural Households in Baringo North Sub-County of Baringo County, Kenya - Kokwon, Costa; Chesambu , Alice; Sumukwo , Joel (African Journal of Education,Science and Technology (AJEST), 2018)
Agriculture is the main contributor to rural livelihoods and food security in developing economies. However, household agricultural productivity and food security is a function of resource investments that are often subjected to gender influences in financial accessibility and ownership of property. This study examines the effects of gender roles on food security among rural households, with intention to providing information that enhances poverty reduction and economic equality among rural households in the area. The study adopted survey design, carried out in Baringo North sub-County with a population of 19,734 with a sample of 127 households, attained through simple random and systematic sampling procedure. The instruments of study were a questionnaire administered to select households. Chi-square method was used to evaluate the factors influencing farm productivity while descriptive data representation was done through frequencies, percentages, tables and charts. The results of the study showed that majority of the respondents (51%) were females while (49%) were male. In terms of household activities females (91%) dominated planting and weeding with men (80%) owning land. Land ownership affects agricultural production as shown by 98% of the respondents in that it tends to affect access to credit and farming activity to be done. Since most of the land is owned by men (80%), they generally influence the type of farming activity done and financial decisions made. Chi square analysis showed that there is a significant relationship between gender roles and food security as p value was less than 0.05,(p=0.000), which means that gender roles in the study area affect household food security, hence women need to be financially empowered to improve food security in Baringo. Also education level and land ownership strongly influence household food security. This study recommends that women be considered to mainstream agricultural development since maximum productivity cannot be met without involving them.